2020
DOI: 10.1108/ec-12-2019-0564
|View full text |Cite
|
Sign up to set email alerts
|

Lichtenberg optimization algorithm applied to crack tip identification in thin plate-like structures

Abstract: Purpose This study aims to develop a numerical identification and characterization of crack propagation through the use of a new optimization metaheuristics called Lichtenberg optimization. Design/methodology/approach The damage-identification problem is treated as an inverse problem, which combines finite element methods with intelligent computational methods to obtain the best possible response. To optimize the objectives, the Lichtenberg algorithm is applied, which includes concepts of random cluster grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The multi-objective Lichtenberg algorithm is a meta-heuristic that has trajectory and population characteristics and was created by Pereira et al (2021a, b, c). The single-objective version of the algorithm was proposed by the same author (Pereira et al, 2020), and the results shown in several works are promising. This metaheuristic has already been used in several optimization cases, for example, in a multi-objective design optimization of a highperformance disk brake using LA (Pereira et al, 2023).…”
Section: Multi-objective Lichtenberg Algorithm Optimization (Mola)mentioning
confidence: 99%
See 1 more Smart Citation
“…The multi-objective Lichtenberg algorithm is a meta-heuristic that has trajectory and population characteristics and was created by Pereira et al (2021a, b, c). The single-objective version of the algorithm was proposed by the same author (Pereira et al, 2020), and the results shown in several works are promising. This metaheuristic has already been used in several optimization cases, for example, in a multi-objective design optimization of a highperformance disk brake using LA (Pereira et al, 2023).…”
Section: Multi-objective Lichtenberg Algorithm Optimization (Mola)mentioning
confidence: 99%
“…The Lichtenberg algorithm (LA) will be used in this step. The LA has had excellent results in several published works; for example, Francisco et al (2022) evaluated the multi-objective design optimization of the double arrowhead auxetic model using LA, fabrication and mechanical characterization of red mud-based AL2025-T6 MMC using the Lichtenberg optimization algorithm and the whale optimization algorithm (Challan et al, 2021), a powerful Lichtenberg optimization algorithm: a damage identification case study (Pereira et al, 2020), Lichtenberg optimization algorithm applied to crack tip identification in thin plate-like structures (Pereira et al, 2020) and design optimizations of carbon fiber-reinforced polymer isogrid lower limb prostheses using particle swarm optimization and the Lichtenberg algorithm (Francisco et al, 2020).…”
Section: Ec 409/10mentioning
confidence: 99%
“…The meta-heuristic, also developed at GEMEC, has been successful in identifying cracks (Pereira et al [2020]) and delaminations (Pereira et al [2021]), isogrid tube optimization (Francisco et al [2020]; Pereira et al [2022a]), hydrogen production optimization (Souza et al [2022]), wind forecast optimization (Tian & Wang [2022]), parameter optimization in manufacturing processes (Challan et al [2022]; Mohanty et al [2022]), and multi-objective optimization (Pereira et al [2022]), among other applications. The LA algorithm in the mono-objective version has already been well explained in previous chapters.…”
Section: Lichtenberg and Multi-objective Lichtenberg Algorithmsmentioning
confidence: 99%
“…The modified mode shape curvature is utilized to study single and multiple damage position in a cantilever beam [27,28]. In a study, the results indicate that the Lichtenberg algorithm, which is solely based on strain fields, provides very accurate crack identification in plates-like structures [29]. A study uses scanning electron microscopy to analyze the morphology and crystalloid salt occurrence state within the pore after measuring the change in porosity and permeability of several tight sandstone samples [30].…”
Section: Introductionmentioning
confidence: 99%